Kebijakan Presiden Indonesia Pada Laut Cina Selatan di Depan Masyarakat Global - Ester Senov Fitriani Simanjuntak; Putri Juliani Br Tarigan; Rizal Sanusi Hasibuan; Vanessa Uli Sembiring; Sri Susanti Simanjuntak; Dahlia Natalia Lumban Gaol; Salsabila Balqis Siregar (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Geographically, the SCS has an area of ​​around 3 million km2 and is located between the southern coast of China and Taiwan to the north, the coast of Southeast Asian countries to the west, a group of islands in the Philippines to the east, and Kalimantan and Indonesia to the south. With the aim of being able to find out more about the Indonesian president's policies regarding the South China Sea dispute in front of the global community, and being able to find out the impact and solutions regarding the Indonesian president's policies regarding the South China Sea dispute in front of the global community. This research uses a qualitative descriptive research design. Library research is research in which data collection is carried out by collecting data from various reference sources. The naming of the North Natuna Sea in the new map reflects Indonesia's foreign policy as a manifestation of Indonesia's national interests in responding to regional developments, and the Indonesian government's efforts to carry out the process of securing territorial sovereignty and its citizens in the seas bordering the South China Sea. Indonesia stated that the SCS conflict could become open war because of three things. First, the tendency of the parties involved to use military force to strengthen claims in the region. Second, there is the involvement of foreign parties from outside the region. Third, there is no credible institution to resolve existing problems.